Regulation of the Immune System in Health and Disease by Members of the Bone Morphogenetic Protein Family - Sconocchia, Tommaso; Sconocchia, Giuseppe (Frontiers in Immunology, 2021)
Bone morphogenetic proteins (BMPs) are potent signaling molecules initially described as osteopromoting proteins. BMPs represent one of the members of the larger TGFb family and today are recognized for their important role in numerous processes. Among the wide array of functions recently attributed to them, BMPs were also described to be involved in the regulation of components of the innate and adaptive immune response. This review focuses on the signaling pathway of BMPs and highlights the effects of BMP signaling on the differentiation, activation, and function of the main cell types of the immune system.